Strengthening collaboration to tackle African swine fever: 'From research to policy' workshop - International Livestock Research Institute (International Livestock Research Institute, 2024)
In this video, Hung Nguyen, lead of the Health Program at the International Livestock Research Institute (ILRI), shares key insights from the workshop ‘From research to policy: Improving animal disease prevention and control in Vietnam’ that took place on 17-18 October 2024 in Quang Ninh Province, Vietnam. The workshop brought together experts, policymakers, and stakeholders to address pressing challenges posed by African swine fever in Vietnam. Through collaborative discussions, participants explored solutions to enhance animal health systems, strengthen disease surveillance, and bridge gaps between research and policymaking.